Enhancing public sector efficiency in Yemen: Human resource management challenges and solutions - Al-aghbari, Areeg Gameel; Baadhem, Abdullah Mahfoudh Salem (Review of Management, Accounting, and Business Studies, 2025)
Yemen's public sector has long struggled with governance deficiencies, bureaucratic inflexibility, and institutional inefficiencies—all of which have been made considerably worse by years of conflict and economic downturn. The strategic use of human resource management (HRM) to improve public sector efficiency in Yemen is critically examined in this research, with an emphasis on the implementation of e-government programs and HRM-driven reforms. To demonstrate how HRM shortcomings in hiring, training, performance management, and employee retention have directly led to systemic breakdowns in service delivery, the study synthesizes empirical data from the transportation, health, education, and food security sectors, drawing on a narrative literature review. The study emphasizes the discrepancy between HRM rules and real administrative results, highlighting the pressing need for merit-based, context-specific, and technology-enabled HRM practices. The results indicate that Yemen's recovery, governance transformation, and development goals will remain unachievable in the absence of extensive institutional reforms, especially in HRM. Strategic suggestions for restoring HR capability, encouraging accountability, and utilizing technology to support sustainable government in Yemen following the crisis.